Determination of Gypenoside A and Gypenoside XLIX in Rat Plasma by UPLC-MS/MS and Applied to the Pharmacokinetics and Bioavailability. (12th August 2022) - He, Yan; Liang, Qishun; Luo, Lvqi; He, Yifan; Huang, Xueli; Wen, Congcong
Abstract : In this work, a UPLC-MS/MS method was developed for the determination of gypenoside A and gypenoside XLIX in rat plasma. For chromatographic separation, a UPLC BEH C18 column was employed, the mobile phase comprised acetonitrile: water (w/0.1% formic acid), and the elution time was 4 min. Detection of each compound was enabled by electrospray ionization in negative-ion mode, and quantitative analysis was enabled by operating in multiple reaction monitoring (MRM) mode by monitoring the transitions of m/z 897.5⟶403.3 for gypenoside A, m/z 1045.5⟶118.9 for gypenoside XLIX, and m/z 825.4⟶617.5 for the internal standard. The calibration curves for gypenoside A and gypenoside XLIX demonstrated excellent linearity ( r  > 0.995) over the range of 2–3000 ng/mL. The intraday and interday precisions of gypenoside A and gypenoside XLIX were within 14.9%, the intraday and interday accuracies ranged from 90.1% to 113.9%, the recoveries were all greater than 88.3%, and the matrix effect ranged from 87.1% to 94.1%. The developed method was successfully applied in the determination of the pharmacokinetics of gypenoside A and gypenoside XLIX. Gypenoside A and gypenoside XLIX had very short half-lives in rats, with oral t 1/2z of 1.4 ± 0.2 h and 1.8 ± 0.6 h, respectively, and low bioavailabilities (0.90% and 0.14%, respectively).